Indexing Versus Journal Ethics - Sorooshian, Shahryar (Springer Netherlands, 2018)
There is a profit if a journal managed to get indexed in a well-recognized database. The encouraging of being an indexed journal might cause an unethical management approaches in some unprofessional journals. This commentary discusses some of the unethical activities which may be done before submission for indexin